2016
DOI: 10.1371/journal.pone.0165634
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Unemployment over the 2000’s: Comparison between People Living with HIV and the French General Population

Abstract: BackgroundDespite improved health, unemployment has increased among people living with HIV (PlwHIV) over the last decade. However, since the economic recession of 2008, unemployment also increased in the French general population. This paper aimed to determine if the increase in the unemployment rate in the HIV population was higher than that in the French general population.MethodsWe used data from the ANRS-Vespa study, a repeated cross-sectional survey among two national representative samples of PlwHIV foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 36 publications
1
15
3
Order By: Relevance
“…Again, an asymmetry in the economic shocks between countries and the different performance of their labour markets will lead to the consequences in that the PlwHIV will differ according to the country and the context analysed. Thus, although our analysis indicates a positive convergence in the employment rate of PlwHIV relative to the general population, employment rates observed at the end of our study period were lower than those observed at the end of the cycle of economic growth (years 2006–2007) and, in any case, they are lower than those observed by Annequin et al [ 29 ] for France in the same years, as the employment rate of PlwHIV in France reached 60% during 2009–2010, while in Spain, it was barely 47%.…”
Section: Discussioncontrasting
confidence: 88%
See 3 more Smart Citations
“…Again, an asymmetry in the economic shocks between countries and the different performance of their labour markets will lead to the consequences in that the PlwHIV will differ according to the country and the context analysed. Thus, although our analysis indicates a positive convergence in the employment rate of PlwHIV relative to the general population, employment rates observed at the end of our study period were lower than those observed at the end of the cycle of economic growth (years 2006–2007) and, in any case, they are lower than those observed by Annequin et al [ 29 ] for France in the same years, as the employment rate of PlwHIV in France reached 60% during 2009–2010, while in Spain, it was barely 47%.…”
Section: Discussioncontrasting
confidence: 88%
“…When we compared our results with those obtained by Annequin et al [ 29 ], we observed that the conclusions are not in line with theirs. While we observed that the differences in employment rate between PlwHIV and general population have decreased during the last decade, they observed that this has increased.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…Such situations might result in a higher rate of unemployment for those living with HIV [86]. Although sparsely reported at present, such cases might add up due to their longer life expectancy and will require increased hospitalization and medical care, thus increasing costs for treatment and welfare.…”
Section: Scenario 2-the Perpetuation Of the Hiv Pandemic?mentioning
confidence: 99%